Length–weight relationships of eight deep‐sea fish species collected from the southwest coast of India. (20th June 2018) - Bineesh, Kinattumkara; Nashad, Musaliyarakam; Aneesh Kumar, K. V.; Akhilesh, K. V.; Hashim, Manjebrayakath
Abstract: Length‐weight relationships (LWR) for eight deep‐sea fishes belonging to six families collected from the south west coast of India are presented. Specimens were caught by deep‐sea shrimp trawls with mesh size 24 mm during 2011 and 2013. The b values ranged from 2.13 to 3.71 and the coefficient of determination ( r 2 ) ranged from 0.84 to 0.98. A new standard length maximum was recorded for Neoscopelus microchir . The b values estimated during the present study were compared with the values estimated using models based on Bayesian approach deposited in Fish Base.